Antibiofilm formation and anti-adhesive property of three mediterranean essential oils against a foodborne pathogen Salmonella strain. (April 2016) - Miladi, Hanene; Mili, Donia; Ben Slama, Rihab; Zouari, Sami; Ammar, Emna; Bakhrouf, Amina
Abstract: Plant extracts, and their essential oils (EOs) are rich in a wide variety of secondary metabolites with antimicrobial properties. Our aim was to determine the bioactive compound in three mediterranean essential oils belonging to Lamiaceae family, Satureja montana L., Thymus vulgaris L. and Rosmarinus officinalis L., and to assess their antimicrobial, antibiofilm and anti-adhesive potentials against a foodborne pathogen Salmonella strain. The antibacterial activity of EOs and its biofilm inhibition potencies were investigated on 2 reference strains Salmonella typhimurium and 12 Salmonella spp. isolated from food. Biofilm inhibition were assessed using the 2, 3-bis [2-methyloxy-4-nitro-5-sulfophenyl]-2H-tetrazolium-5-carboxanilide (XTT) reduction assay. The analytical data indicated that various monoterpene hydrocarbons and phenolic monoterpenes constitute the major components of the oils, but their concentrations varied greatly among the oils examined. Our results showed that S. montana L. and T. vulgaris L. essential oils possess remarkable anti biofilm, anti-adhesive and bactericidal properties, compared to R. officinalis EO. There is an indication that Rosmary EO might inhibit biofilm formation at higher concentrations. Therefore, the witer savory and thyme EOs represent a source of natural compounds that exhibit potentials for use in food systems to prevent the growth of foodborne bacteria and extend the shelf life of the processed food. Highlights: Chemical composition of three medeterranien essential oils (EOs). EOs rich in phenolic compounds (carvacrol and thymol) had excellent anti-bacterial activities. Inhibition of biofilm formation to biotic and abiotic surfaces of different EOs. The food isolated Salmonella spp. strains was more resistant that the reference strain to EOs activity. EOs had the potential to be used as food preservatives and natural protection against foodborne pathogenic bacteria.